PENYULUHAN DEMAM BERDARAH DANGUE (DBD) KEPADA REMAJA GMI MANNA MARTURIA TANJUNG SARI - Damanik, Irene R. Tua; Simanjuntak, Harry C.; Panjaitan, Budi J.; Veronika, Agustina; Pakpahan, Edwin A.; Sihombing, Ferry G.; Yosephine, Kathleen I.; Sitepu, Elvindo W. A.; Siagian, Fevi Yolanda; Br Nainggolan, Nova A.; Nainggolan, Hotlin C.; Br Aruan, Sella A.; Tarigan, Billy C.; Zandroto, Sofi A.; Joris, Letisya Feronika (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Community Service is a form of student activity which is a way of student interaction with the community and the surrounding environment. The topic taken was Dangue Hemorrhagic Fever (DHF), this topic was deliberately chosen considering that currently it is the rainy season where rainfall is very high. Education about Dengue Hemorrhagic Fever (DHF) is important to increase public awareness about the prevention and management of this disease. The aim of FK-UMI Community Service is to provide counseling and provide education to the public regarding dengue fever. The method used is to convey public education information using projectors and interactive media. Conclusions obtained. With this health education, teenagers will understand how to improve their quality of life and maintain a clean environment to avoid dengue fever